MODELS OF PARTICIPANTS INTERACTION OF THE EDUCATIONAL ENVIRONMENT USING THE TOOLS OF AUGMENTED AND VIRTUAL REALITY IN AN INSTITUTION OF GENERAL EDUCATION - Soroko, Nataliia; Tkachenko, Vitaliy (Physical and Mathematical Education, 2023)
The development of information and communication technologies have caused to serious changes in traditional educational concepts, educational models and even education systems.Problem formulation Gradually, attention is drawn to education that is not subject to the traditional concept and frees the participants of the educational process from limitations in time and space, providing a wealth of teaching and learning resources. Virtual and augmented reality technologies are of particular importance. It is necessary to analyze the interaction of participants in the educational process using virtual and augmented reality, when introducing these technologies into educational programs that have a distance equivalent. Materials and methods. We used the following methods to achieve the goal of the study: systematic and comparative analysis of pedagogical, psychological, philosophical, sociological works, methodological and specialized literature; analysis of pedagogical experience of use . virtual and augmented reality technologies of the educational in general secondary education institutions; questioning teachers about their experience of using  virtual and augmented reality technologies in the educational process, identifying problems for the creation of special webinars and courses in order to develop digital competence of teacher; interpretation of research results. The research was carried out within the framework of the research work “Designing the learning environment using augmented and virtual reality tools in general secondary education institutions” (DR № 0121U107689) of the Institute for Digitalisation of Education of NAES.Results. It has been established that the interaction of participants in the educational process using virtual reality technology requires improvement, methodological recommendations, and research on the organization of this environment for various purposes. For example, students' exploration of new educational material, conducting laboratory work, collaborative student research, providing instructional guidance for teachers working with students in virtual learning environments, etc. The interaction of participants in the educational process using augmented reality is better understood by teachers and students. They utilize both ready-made augmented reality technologies and personally created ones.Conclusions. It has been determined that the model of interaction among participants in the educational process of a general education institution, using virtual and augmented reality, generally includes the following blocks: the teacher's activity in organizing the interaction of participants in the educational process using virtual and augmented reality; the organization of interaction between students and the teacher using virtual and augmented reality; the main types of interaction among participants in this process using virtual and augmented reality; the assessment of the effectiveness of interaction in an educational project with virtual and augmented reality. Moreover, the model of interaction among participants in the educational process using virtual reality should take into account the characteristics of the space designated for the use of virtual reality and aim for maximum coverage relative to the center of the classroom.
Keywords: virtual reality; augmented reality; participants interaction in the educational environment; model of participants interaction in the educational environment